2021
DOI: 10.1007/s10964-021-01480-6
|View full text |Cite
|
Sign up to set email alerts
|

What Happens After School? Linking Latino Adolescents’ Activities and Exposure to Community Violence

Abstract: Although community violence and the deleterious behavioral and psychological consequences that are associated with exposure to community violence persist as serious public health concerns, identifying malleable factors that increase or decrease adolescents' risk of exposure to community violence remains a significant gap in our knowledge base. This longitudinal study addresses this research gap by investigating adolescents' endorsement of familismo values and participation in three types of after-school activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 42 publications
(60 reference statements)
0
15
0
3
Order By: Relevance
“…Such programs can center around community and self-esteem-building exercises to problematize and prevent impulsive, reactionary responses to perceived slights (McCrea et al, 2019). One study of Hispanic adolescents’ risk of exposure to violence (Ceballo et al, 2021) found that more frequent participation in nonstructured community-based activities increased the risk of victimization and of witnessing community violence, fueling the violence/retaliation cycle. This points to the importance of more structured, supervised after-school activities for adolescents, namely ones that show the benefits of an affirming, collaborative disposition (e.g., team-based exercises).…”
Section: Discussionmentioning
confidence: 99%
“…Such programs can center around community and self-esteem-building exercises to problematize and prevent impulsive, reactionary responses to perceived slights (McCrea et al, 2019). One study of Hispanic adolescents’ risk of exposure to violence (Ceballo et al, 2021) found that more frequent participation in nonstructured community-based activities increased the risk of victimization and of witnessing community violence, fueling the violence/retaliation cycle. This points to the importance of more structured, supervised after-school activities for adolescents, namely ones that show the benefits of an affirming, collaborative disposition (e.g., team-based exercises).…”
Section: Discussionmentioning
confidence: 99%
“…This is likely to be a consequence of the school age of the study cohort (with a median age of 16 years) and is in keeping with the findings of previous investigations of stabbings in young people in the UK [ 26 ]. There are some reports in the literature that propose structured after-school activities [ 27 ] including sports and leisure interests [ 28 ] to prevent violence in vulnerable groups. These kinds of activities may be community interventions that deserve further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Among Black adolescents primarily from families with low incomes, maternal racial socialization messages weakened the relations between exposure to community violence and both aggressive behaviors and depression (Henry et al, 2015). Likewise, among Latino adolescents from families with low incomes, endorsement of familismo was linked to lower levels of exposure to community violence, and familismo buffered adolescents from the association between this exposure and symptoms of depression (Ceballo et al, 2021; Kennedy & Ceballo, 2013). Racial/ethnic socialization and familismo may protect these youth precisely because they correspond with their intersectional identities.…”
Section: Theoretical Framework and Looking Aheadmentioning
confidence: 99%
“…It is not inevitable that a public health crisis in which disproportionate numbers of racial/ethnic‐minority youth from families with low incomes are exposed to extremely high rates of community violence continues unabated. Yet few studies have examined the malleable factors, whether behavioral, contextual, or cultural, that decrease children’s and adolescents’ likelihood of experiencing community violence in the first place (among those that have are Burnside & Gaylord‐Harden, 2019; Ceballo et al, 2021; Kennedy & Ceballo, 2013; Lambert et al, 2013). Clearly, more work is needed.…”
Section: Theoretical Framework and Looking Aheadmentioning
confidence: 99%